Physical activity barriers and team cohesiveness of Angeles City volleyball players during the pandemic - Fernadez, Rainer; IbaÃ±ez , Sandra; Rotas, Jhon Clifford; Velasco, Rufino Jr; Lobo, Joseph; Celis, Michael Louie (Edu Sportivo: Indonesian Journal of Physical Education, 2022)
Physical activity barriers, particularly for the volleyball players of Angeles City, are one of the elements that hinder team cohesiveness for all athletes during this pandemic. According to research, there are many areas where the pandemic influences physical activity and team cohesiveness. The purpose of this study is to ascertain whether physical activity barriers have a direct impact on volleyball players' ability to work together as a team. Based on related literature on how it affects physical activity barriers, an online Cross-Sectional, Descriptive-Survey research was conducted on the volleyball players around Angeles City. Respondents were chosen based on specific qualities and criteria and provided unbiased selection. In analyzing the data, the pandemic practices and communication are the areas that impact the volleyball players in the middle of the pandemic. The findings showed that physical activity barriers have no association with the team cohesiveness of the volleyball player. It is suggested to the trainers, coaches, school administrators, and players that they can apply the findings of this study to their training amidst this pandemic. For further validation, the same research is needed to identify the other areas or factors that affect physical activity barriers to team cohesiveness.